La Agenda 2030, el Derecho Global y el Derecho Internacional - Ana Manero-Salvador (Revista Iberoamericana de Estudios de Desarrollo)
There are not few authors who speak of a crisis in International Law. Some even propose alternative regulatory frameworks. One of those that has had the greatest projection is the one proposed by Kinsgbury, Krisch and Stewart regarding Global Administrative Law or Global Law. On the other hand, the 2030 Agenda constitutes a milestone that marks international relations in our days, hence this work addresses how the 2030 Agenda could be framed in the Global Law proposal. Likewise, it is researched if we are facing a new legal framework, or if, on the contrary, International Law has a great capacity for adaptation, so we would be facing a flexible International Law, in which the 2030 Agenda would be framed.